2000
DOI: 10.1046/j.1365-2516.2000.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful surgical treatment of haemophilic pseudotumour, filling the defect with hydroxyapatite

Abstract: A preliminary report is made on the use of hydroxyapatite for surgical procedure of pseudotumour, a rare but serious complication of the bleeding diathesis in patients with inherited bleeding disorders. Surgical or percutaneous treatment and refilling with fibrin sealant is shown to be a successful therapy in a 19-year-old male with severe haemophilia B. The pseudotumour, in the upper pad of the left leg, was filled with hydroxyapatite after surgery. We suggest that the use of hydroxyapatite is a new and usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Percutaneous curettage and filling with hydroxyapatite has been described by Sagarra et al . [14], who reported one case in which they filled the residual cavity with hydroxyapatite. This was manufactured from coral skeletal carbonate via a hydrothermal exchange procedure, which preserves the porous interconnecting structure.…”
Section: Percutaneous Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous curettage and filling with hydroxyapatite has been described by Sagarra et al . [14], who reported one case in which they filled the residual cavity with hydroxyapatite. This was manufactured from coral skeletal carbonate via a hydrothermal exchange procedure, which preserves the porous interconnecting structure.…”
Section: Percutaneous Managementmentioning
confidence: 99%
“…In adult patients, filling the defect with bone graft or fibrin glue via the percutaneous insertion of a trocar into the cyst has been recommended by Caviglia et al [13]. Percutaneous curettage and filling with hydroxyapatite has been described by Sagarra et al [14], who reported one case in which they filled the residual cavity with hydroxyapatite. This was manufactured from coral skeletal carbonate via a hydrothermal exchange procedure, which preserves the porous interconnecting structure.…”
Section: Curettage and Filling With Fibrin Seal And Cancellous Bone Gmentioning
confidence: 99%
“…Different therapy options have been described in the treatment of the haemophilic pseudotumour including surgical resection, arterial embolisation, radiotherapy, percutaneous curettage, and filling with fibrin and/or bone graft or hydroxyapatite [2,3,[10][11][12][13][14][15][16][17]. However, treatment of the haemophilic pseudotumour poses a challenge, and extensive clinical experience is essential to appropriately address this serious complication in patients with haemophilia.…”
Section: Introductionmentioning
confidence: 99%
“…This is not always possible as there may be destroyed bone. The peripheral pseudotumors are easily treated by the opening of a bone window, the drainage and curettage of the contents and then the packing of the pseudotumor space with bone and/or bone substitutes [11] mixed with glue [12]. Bony structures, e.g.…”
Section: Realistic Aimsmentioning
confidence: 99%